Stretch, fold, and break: Intensification of emulsification of high viscosity ratio systems by fractal mixers. Issue 5 (22nd February 2021) - Hofmann, Martin; Bayles, Alexandra V.; Vermant, Jan
Abstract: During emulsification process design, the bulk and interfacial rheology of the target formulation must be carefully considered. Formulations with high viscosity ratios and/or finite interfacial elasticity are particularly challenging to emulsify, as conventional drop‐breakup methods consume significant energy and provide limited control over polydispersity. Here, we develop a two‐stage process that produces monodisperse emulsions from high viscosity ratio constituents. In the first stage, a custom static mixer generates co‐flowing layers of alternate phases, and progressively thins layers until they rupture, thus forming a high‐internal phase emulsion. The interfacial properties and flow conditions that promote stable fractal multiplication are discussed. In the second stage, extensional flow elements refine the polydispersity. We demonstrate the utility of this novel process by producing remarkably monodisperse polyisobutylene‐in‐water emulsions with an energy efficiency that is orders of magnitude higher than classical emulsification methods. The moderate throughputs achieved show promise for upscaling and intensification in industrial applications.